PREPARAÇÃO E CARACTERIZAÇÃO DE NANOPARTÍCULAS DE PLATINA INCORPORADAS AO POLÍMERO CLORETO DE 3-n-PROPILPIRIDÍNIO SILSESQUIOXANO - Santos, Vagner dos (2009)
This work describes the preparation of platinum nanoparticles using the inorganic polymer 3-n-propylpyridine sylsesquioxane chloride (SiPy+Cl-) as nanoreator and stabilizer. The system comprising the metallic nanoparticle and the SiPy+Cl- (called hybrid Pt-SiPy+Cl-) was obtained by chemical reduction of H2PtCl6 in the presence of SiPy+Cl-, using formic acid as reducing agent. The formation of platinum nanoparticles was monitored by UV-vis spectroscopy by measuring the decrease in the intensity of the band in ca. 375 nm attributed to the electronic absorption of PtCl6 -2 ions. The average size of the nanoparticles was determined by transmission electron microscopy (TEM) and is between 3 and 40 nm. The hybrid Pt-SiPy+Cl- was used as a polycation in the preparation of layer-by-layer (LbL) films on FTO substrate (tin oxide doped with fluorine), alone, or being alternated with polyanion polyvinylsulphonic acid (PVS). Measurements of cyclic voltammetry obtained from prepared films confirmed the incorporation of metallic platinum in the polymer SiPy+Cl-, as can be seen by the adsorption and desorption of hydrogen in potential regions characteristics for platinum. The electrodes containing LbL films of Pt-SiPy+Cl-/PVS and PVS/Pt-SiPy+Cl- were tested as catalyst for dopamine (DA) oxidation at different concentrations (1.0x10-6 mol L-1 to 2.17x10-3 mol L-1). The film containing 12 LbL bilayers of PVS/Pt-SiPy+Clpresented the greater homogeneity in the distribution of material on substrate, as determined by atomic force microscopy (AFM). The former also has the better response for the electrochemical determination of DA in concentrations lower than 1.0x10-5 mol L-1 (greater sensitivity) when compared to electrodes made of: a LbL film containing only the hybrid, a platinum plate and a FTO plate. Moreover, the limit of detection (LOD) for DA using the LbL film containing 12 bilayers of PVS/Pt-SiPy+Cl- was in the order of 1.0x10-5 mol L-1, while the other electrodes showed higher values. These results indicate that the application of this electrode formed by LbL films illustrate a new material for DA electrochemical detection, generating the possibility of replacing the conventional platinum electrodes. Moreover, in the future, there is the possibility of the application of this LbL film electrode as a sensor for in vivo DA detection.